Material Use in Collaborative Dialogue by Japanese University Students Learning Future Tenses in French as a Foreign Language: A Discourse and Interaction Analysis - Renoud, Loïc (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2022)
This article reports on the use of an experimental material to enable discrimination between the periphrastic future (PF) and simple future (SF) intended for initial level university students in Japan studying French as a Foreign Language. A dyad was filmed using the material in a task on tense choice in short dialogues modelled on Galperin’s procedure. A discourse and interaction analysis were then performed on excerpts of the videoed session where the participants interacted with the material. It was found that the material enabled the dyad to complete the task. Moreover, if the pragmatic effect of the SF was not fully grasped, the analysis nonetheless showed that the participants transformed the linguistic knowledge from the material into metalinguistic resources of their own, and that internalization of the targeted concepts occurred to some extent.